Numb chin syndrome as a presenting central nervous system metastasis of prostate cancer: A case report (Annals of Medical Research, 2023)
A 71-year-old male who has prostate adenocarcinoma, was admitted to the medical oncology clinic with fatigue and intermittent epistaxis. He had anemia, thrombocytopenia, and increased lactate dehydrogenase levels in his blood. He had numbness in the chin and lower lip. Brain MRI revealed findings supportive of leptomeningeal disease. Numb Chin Syndrome (NCS) is also known as mental nerve neuropathy and is a rare sensory neuropathy. There are many benign and malign etiologic factors for this rare syndrome. This syndrome may be the first sign of systemic cancer or advanced manifestation of known cancer, both have poor prognosis. We present a case with NCS associated with prostate cancer with leptomeningeal metastasis.NCS is a rare syndrome, that can develop due to benign or malignant diseases. NCS may be the first sign of the underlying malignancy, and sometimes it can be a sign of progression or recurrence of underlying malignancy. Leptomeningeal metastases of prostate cancer are extremely rare. All patients with NCS with or without malignancy should keep in mind the possibility of both jaw and cranial malignancies and investigated accordingly.
Keywords: Mandibula; Cancer; Neuropathy; Paresthesia